Chattogram Hill Tracts Under the Alleged Threat: An Overview - Iqbal, Masud; Ushama, Thameem (Advances in Social Sciences Research Journal, 2022)
This article describes the plots of Christian missionaries and NGOs in Chattagram Hill Tracts. Some selected methods of NGOs are highlighted by mentioning international propaganda. The activities of Christian missionaries have been analysed since before the British colonial rule. The relationship of the missionaries with the British rulers is brought out in the light of the analysis. It reveals the deep conspiracy behind the evangelism of Christian missionaries and the human services of NGOs. The secret missions of intelligence agencies are highlighted. The Chittagong Hill Tracts-related nefarious scheme and propaganda have been exposed. The political step of the Christian mission is also brought to light. The conspiracies collaborating with some tribal groups and intelligence agencies are discussed. It also unveils the incitement of anti-Islamic movements among the Christian missionaries and NGOs among the tribal people of CHT.